A comparative approach in the utilisation of rice husk and empty palm bunch in the biomass boiler. Issue 1 (November 2021) - Kaniapan, Sivabalan; Nesan, Kartikeyan Patma; Ya, Hamdan; Hassan, Suhaimi; Buang, Azizul; Safuan Zakaria, Mohd
Abstract: Growing world's population has immense contribution towards world economy and energy utilisation. The enormous usage of conventional fuel has contributed many environmental problems such as greenhouse gas emission (GHG), world climate change, and deterioration of human health. Recent study focuses on the generated power from EPB compared with methane in a typical biomass boiler. Also, there are very limited studies on the Air to Fuel (ATF) ratios value in boiler operation. In this paper, empty palm bunch (EPB) and rice husk (RH) have been selected as biomass fuel in the biomass boiler. The same recommended parameters of boiler and turbine was chosen for both EPB and RH feedstocks from previous study. Overall, the study proven to produce about 33% and 25% of energy from EPB and RH of what a methane (CH4) can produce from the same amount of feeding rate, respectively, with EPB producing 13.31% of higher turbine power than RH. This directly contributes to the technical feasibility and adaptability of environmentally friendly elements by seizing the opportunity of carbon emission of conventional fuel and replacing it with natural resources such as EPB and RH which are part of the biomass fuel replacement regime. However, ATF ratio of RH is significantly minimal of what a CH4 and EPB utilised to burn 1 kg of fuel. Therefore, EPB and RH would be suitable for future renewable biomass feedstock in comparison with conventional fuel for power generation purposes.